Comparing the functional and pasting properties of gari and the sensory attributes of the eba produced using backslopped and spontaneous fermentation methods - Awoyale, W.; Oyedele, H.; Adenitan, A.A.; Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie (Informa UK Limited, 2021)
The possibilities of backslopped fermentation replacing spontaneous fermentation in gari production were evaluated by comparing the functional and pasting properties of gari and the sensory attributes of the eba. Backslopped cassava mash (BCM) was produced from 75 kg of TMS13F1343 cassava roots by pre-fermenting for 96 h. The BCM was mixed with fresh cassava mash (FCM) from another 75 kg of the same variety using design expert software developed blend ratios and processed to backslopped fermented gari (BFG). Another batch of 150 kg of the same variety was processed to gari by spontaneously fermenting for 24 h, 48 h, 72 h and 96 h (SFG). All the gari samples were analysed for functional, pasting and sensory properties and physical colour using standard methods. Results showed that a significant difference (p < 0.05) exists in the whiteness, dispersibility and water absorption capacity of the 24 h SFG compared to that of the BFG. All the pasting properties of the 48 h SFG were significantly different (p < 0.05) from that of the BFG. Only the texture differentiates (p < 0.05) the 96 h SFG eba from that of the BFG eba. The outcome of this study may be used by cassava processors/value chain actors to produce an acceptable BFG of different qualities within a day, and whose quality may be comparable or better than the SFG.